Methods and tools used by healthcare professionals to identify barriers to return-to-work for workers with upper extremity conditions in Australia. (March 2017) - Peters, Susan E; Johnston, Venerina
Introduction: Healthcare professionals, including hand therapists, are frequently called upon to identify barriers to return-to-work for workers with upper extremity injuries. However, the methods and tools used to assess barriers to return-to-work remain unknown. Results from these assessments can be used to direct appropriate interventions for those who may be at risk of a prolonged work absence. Methods: The purpose of this study was to identify the tools and methods used by healthcare professionals to assess barriers to return-to-work for workers with upper extremity conditions. A total of 596 Australian healthcare professionals responded to an open-ended question regarding the tools/methods they use to identify barriers to return-to-work. All responses were coded and analysed descriptively. Differences between professional disciplines were recorded. Results: Healthcare professionals nominated 59 types of tools and methods that they use to identify barriers to return-to-work for workers with upper extremity conditions in their clinical practice. The most favoured method was clinical interviewing. Other commonly used tools were clinical measures, e.g., strength, and a return-to-work risk-factor screening tool validated on musculoskeletal diagnoses, the Orebro Musculoskeletal Screening Questionnaire. Discussion: Healthcare professionals use a variety of methods and tools to identify barriers to return-to-work for workers with upper extremity conditions. Generally, they favoured subjective methods. Future research is needed to develop or validate assessment tools designed to identify barriers to return-to-work for workers with upper extremity conditions. In the absence of upper extremity specific screening tools, hand therapists should consider the biopsychosocial framework when evaluating barriers to return-to-work.